PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR SISWA MATERI KALOR SMA NEGERI 1 ANGKOLA TIMUR - Sari, Lia Purnama (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2023)
This study aims to determine the improvement of student physics learning outcomes in caloric material by using cooperative learning model TGT type. The population in this study are all students of class X in SMAN 1 Angkola Timur which amounts to 95 students. So the sample research used is the total sample. The research method used was quasi experiment with two pretest-posttest design studies. Researcher determine which become experiment class in this research is class X1 and control class in this research is class X3. Technique of collecting data using observation and test. While the data analysis using t-test. Based on the calculation, cooperative learning model type TGT meteri calor obtained an average value of 87.5% is in the category of